Electrochemical detection of ampicillin and vancomycin using nickel nanoparticle modified electrode - Salihu, Suleiman (2019)
Ampicillin and vancomycin are chemical substances used as antibiotics to treat and prevent disease development. The conventional methods used in detecting these residues suffered some drawbacks of being expensive, time consuming and lack the capacity for point of care analysis.In this work technological detection based on nickel nanoparticle (NiNP) was developed. NiNP was synthesizedusing hydrazine, polyvinylpyrrollidone, aqueous sodium hydroxideand 3-aminopropyl-triethoxysilane (APTES) as a crosslinker is presented here. The amine groups in APTES were used as growth point for the NiNP synthesis through electrostatic attraction between the amine group (NH4 +) and Ni(II) chloride- while sodium hydroxide acts as a reducing agent. Nickel nanoparticle has properties ofconductivity and catalytic particles that is intensively exploited for electrode modification.The synthesized particle demonstrates average size distribution of nanoparticle of about 50 nm. The energy dispersive X-ray was conducted to find the elemental composition of the nanoparticle while X-ray diffraction measurement identify the phase and crystallinity of nickel nanoparticle. The Field emission scanning electron microscopy reveal that the formed nanoparticle are dominantly spherical in shape and evenly distributed. The attachment of the carboxylic group(-COOH) to the surface of nanoparticle is confirmed by FTIR. As evidenced by electrochemical measurements, these surface nickel nanoparticle generates substantial surface area. For bare SPCE, the active surface area was calculated to be 0.034 cm2 while the effective surface area of modified SPCE with nickel nanoparticle was found to be 0.084 cm2. Effect of parameters such as pH, buffer, scan rate, accumulation potential, accumulation time and concentration on the sensitivity of fabricated sensor were optimized. Under the optimized conditions, there were two linear calibration ranges from 0.01–0.5 μM with regression equations of Ip(μA) = 350.749C + 1.0443, correlation coefficient of 0.9996 for ampicillin and Ip(μA) = 340.618C + 14.704 correlation coefficients of 0.9993 for vancomycin, respectively. Moreover, an excess of a quadratic mixture of amoxicillin, penicillin G, Vancomycin, changed less than 5.0 % of the ampicillin signal. This suggests that the fabricated sensor has a satisfactory selectivity for determination of ampicillin and vancomycin. The reproducibility and stability of NiNP were investigated using cyclic and differential pulse voltammetry measurements of 10 μM ampicillin and vancomycin. The relative standard deviation (RSD%) for seven successive assays of ampicillin and vancomycin was 1.83 and 1.92. When the electrode was stored in the laboratory at room temperature to determine its stability, the modified electrode retained 87% and 85% their initial response for a period of 28 days. These results indicate that NiNP on SPE has good stability and reproducibility, and can be used to detect antibiotics at low concentration either in waste or food samples. The 10 μM of ampicillin and vancomycin under the optimized conditions were used to determine the interference of other species. The results obtained indicate that the interference species have less than 5% peak currents in each analysis. The limit of detection and limit of quantitation for ampicillin were calculated as 0.00031 μM and 0.00300 μM, and that of vancomycin is 0.00041 μM and 0.00135 μM respectively. The developed electrochemical sensor based on nickel nanoparticle modification system and Aptes as a binder is applied in the detection of the antibiotics.